The Search for God's Law - Yusuf Talal DeLorenzo (International Institute of Islamic Thought, 1994)
When one works in the field of Shari'ah studies, a field widely perceived as holding little excitement (for those who pursue careers in it and for those who don't), one rarely encounters a book that sends one into the poetic ecstasy of a Keats, for example, on the occasion of his first looking into Chapman's Homer. Nonetheless, in any intellectual enterprise there are joys that perhaps only the initiated, so to speak, may truly share. In fact, in the field of Shari'ah studies, as in many of the fields related to the study of classical Islamic disciplines, the esoteric delights to be tasted these days are many, particularly in view of the continual stream of carefully edited works from the classical period ... especially when so many of them were believed lost, eaten by worms in some dreary desert setting or sent tumbling toward eternity in the bloody waters of the Tigris when Baghdad was overrun by Mongol hordes. But, to return to the present, it is certainly not everyday that something really significant happens in the field. In The Search for God's Law, that significant something has happened. Less than a decade ago, a distinguished western scholar lamented in the Journal of the American Oriental Society that "despite the great interest shown in U$iil al fiqh by Orientalists throughout the world, no general and systematic work dealing with this most important Islamic ...